1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Can someone explain to me what he is doing here, transformation matrices, weee

  1. Dec 2, 2005 #1
    Hello everyone, i posted 2 pictures, they are the same problem, just couldn't fit it.
    http://img222.imageshack.us/img222/1227/lastscan5vx.jpg
    http://img222.imageshack.us/img222/1681/lastscan29fm.jpg

    I don't understand the majority of the steps, like hwy does he multiply
    2*[1 2] - [2 1] = 3j?
    also
    he then says
    j = 2/3[ 1 2] - 1/3[2 1] ?
    this one really doesn't make sense:
    i = [1 2] - 2(2/3*[1 2] - 1/3[2 1])
    The examples in the book are easy and i understand then, they always had either i given to u or j given to you. like
    T[ 1 0] = [2 -3] but this one doesn't give u anything so i know u have to manipulate the matrices to get the standard, i = [1 0] j = [0 1] but i'm confused on his logic behind it, can someone explain to me why he did what he did'? thanks!
     
  2. jcsd
  3. Dec 2, 2005 #2

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    He has already said that i= [1 0] and j= [0 1]. [a b]= [a 0]+ [0 b]= a[1 0]+ b[0 1]= ai+ bj. 2*[1 2]- [2 1]= [2 4]- [2 1]= [2- 2 4- 1]= [0 3] which is just another way of writing 0i+ 3j= 3j.
    (2/3)[1 2]- (1/3)[2 1]= [2/3 4/3]- [2/3 1/3]= [2/3- 2/3 4/3- 1/3]=
    [0 1]= 0i+ 0j
    We've already established that (2/3)[1 2]- (1/3)[2 1]= [0 1] so
    [1 2]- 2((2/3)[1 2]- (1/3)[2 1])= [1 2]- [0 2]= [1-0 2- 2]= [1 0] which is the same as i.
    One more time, i is just a short way of writing [1 0], j is just a short way of writing [0 1]. "ai+ bj" is a short way of writing [a b].
     
  4. Dec 3, 2005 #3
    Thank you so much Ivy, that made alot more sense, I worked through it again and i'm stuck on this part, I understand all the steps to get to 3j; or [0 3] = 0i + 3j = 3j;
    But then we go into another series of calculations to get it to [0 1] which is just j. Was the point of finding 3j first, so you could perform the following calculation?
    2/3[1 2] - 1/3[2 1]? since u found 3j, u know u can get [0 1] by multplying by 1/3? so is that why u have the -1/3? And ur multpying 2/3 by [1 2] because ur trying to get a 0 on top and a 1 on the bottom right? so u get [0 1] which is ur j. Is my reasoning right? Thanks again!

    I just added to this post, i think i get the top part, but this one really doesn't make sense:
    he writes:
    i = -1/3[1 2] + 2/3[2 1] = [1 0] yes i see that it equal i, but how does that relate to all the work we just did above to find i and j? Because we orginally wrote to find i, we had i = [1 2] - 2(2/3[1 2] - 1/3[2 1]) = [1 0] = i; but then he writes:
    i = -1/3[1 2] + 2/3[2 1] which isn't what we had above?
     
    Last edited: Dec 3, 2005
  5. Dec 4, 2005 #4
    Wow, 2 hours of working through examples and i finally figured out whats going on with transformations! thanks for the help you were telling me the right way, it was just going in and my brain was like f it. :)
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?



Similar Discussions: Can someone explain to me what he is doing here, transformation matrices, weee
Loading...